ANALISA DAN IMPLEMENTASI KNOWLEDGE MANAGEMENT SYSTEM: STUDI KASUS DI SEKOLAH MENENGAH ATAS NEGERI 1 BAYANG - Putra, Ondra Eka (Sainstek : Jurnal Sains dan Teknologi, 2015)
Found lack of good management of knowledge School SMA Negeri 1 Bayang. Knowledge management is not good can cause a lack of knowledge transmission is only delivered directly. This is because the learning activities are only delivered face to face. Knowledge is one thing that is very important for students, teachers and employees at the school, the knowledge does not have to be obtained in person or face-to-face between teachers, students and employees who share knowledge. In this study will be designed a system that can manage knowledge so well that teachers, students and employees can share knowledge and information for the actors who needs although do not follow the forum directly to the knowledge management system, when students can not attend classes can still get the material from integrated system, delivery of information by the school can also be obtained by students although unable to attend school, the teacher can not attend a workshop or meeting can get the information or the results of the workshop or meeting.Key words: knowledge management system, knowledge sharing and information